Investigating the recruitment, interactions, and activity of Polycomb proteins in development and disease. - Tuck, Ellen (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2024)
Polycomb group proteins are chromatin regulators associated with transcriptional repression of developmentally important genes. They assemble into multiprotein complexes, including Polycomb Repressive Complex 1 (PRC1) and 2 (PRC2). PRC2 is a histone methyltransferase complex responsible for the methylation of H3 lysine 27 (H3K27me1/2/3). PRC2 consists of a trimeric catalytic core which associates with facultative subunits that mediate the recruitment of PRC2 to target sites on chromatin. These subunits associate with the core in specific, mutually exclusive combinations, forming the PRC2.1 and PRC2.2 subcomplexes. The aim of this thesis is to investigate the function of specific PRC2 proteins in stem cells and in human developmental disorders. First, I explore the contribution of PRC2.2 protein JARID2 in recruitment of the complex to target sites via its ubiquitin interaction motif which is known to bind to PRC1-mediated H2AK119ub1. I discover that the requirement of the JARID2 UIM for recruitment of PRC2.2 varies at different Polycomb target sites. Next, I examine the dependence of PRC1 protein, CBX7, on JARID2 for recruitment to chromatin. I discover that the PRC2-independent C-terminal portion of JARID2 is necessary and sufficient for CBX7 binding at Polycomb targets. I analyse the protein interactome of JARID2 and CBX7, revealing that CBX7 recruitment is not mediated by a direct protein interaction with JARID2. However, this proteomic analysis does reveal an unexpected direct interaction between JARID2 and PRC2.1 protein MTF2, which I believe indicates the existence of another PRC2 subcomplex, referred to as PRC2.3, which has thus far been overlooked in the field. I also dissect the interaction between PRC2.1 protein, PALI1, and the H3K9 methyltransferase, G9a, identifying a histone mimic motif in PALI1 that drives the interaction. Finally, I generate mouse embryonic stem cell models of mutations in PRC2 core component, SUZ12, that cause the human overgrowth and intellectual disability syndrome, Imagawa Matsumoto syndrome. I characterise the effects of these mutations on PRC2 activity, identifying loss-of-function and dominant-negative alleles. Taken together, the work presented in this thesis contributes to a better understanding of the recruitment of Polycomb complexes to chromatin, their interactions with other chromatin regulators and their dysregulation in developmental disorders.
APPROVED
Keywords: Polycomb; Chromatin; PRC2; PRC1; Imagawa Matsumoto Syndrome